Data-driven QCD background estimation to W production in association with jets using the ATLAS detector - Radovanovic, Lidija (Department of Physics, 2017)
A preliminary analysis was conducted using data from the proton-proton collisions at p s = 8 TeV recorded by the ATLAS experiment, corresponding to an integrated luminosity of approximately 18.9 ƒƅ⁻¹. It has been performed to extract the fraction of QCD events in the chosen phase space for the W boson production in association with jets. A data-driven technique was developed for measuring the QCD background. The fraction of QCD events in the signal region was estimated in exclusive jet multiplicities by performing an extended likelihood fit on the Emiss T distribution in data. The fraction of QCD events ranges 2:9 ± 0:01% for the zero jet bin and increases to 10:74 ± 0:11% for the two jet bin.The fraction of QCD events decreases with increasing jet multiplicity. Using the results from the fit, some important kinematic distributions have been made. The overall agreement between the data and Monte Carlo simulation is vastly improved by including the data-driven QCD background estimate. This agreement could be further improved by using a data-driven tt estimate where the tt MC tends to overestimate the amount of events in the higher jet multiplicities.